PSYCHOLOGICAL NATURE OF THE ART OF AITYS - Berdibayeva S.K.,; Syrgakbayeva A.S.,; Abdualiyev A.Z.,; Berdibayev S.K.,; Garber A., (Scientific Journal of Pedagogy and Economics, 2020)
The main purpose of present research was to investigate the psychological nature of Kazakh Aitys and it’s impact to personal development, ethnocultural values and other skills of Kazakh young People, which required by modern market world. Also the opportunity of creating the communicative and interactive model of creative process of Aitys is considered. According to the results of the present research there are considered that the Aitys is a jont dialogical creative cognitive activity, which psychological structure has communicative-interactive nature and depends on Kazakh ethnic picture of the world. Aitys as a kind of folklore has a change trends. Process of communication in the Kazakh ethnos has it's features. Aitys isn't result and a victory of one person during competition, since Aitys is result of joint creativity of listeners and poets, because they are representatives of the same ethnos. With the influence of an Aitys uniform ethnic integrity of the Kazakh people is created. During an Aitys there is a co-authorship, empathy of the same problems and conditions of the people. Aitys introduces novelty and according to the contents it leads to particular change in human minds. In the intellectual sphere of young people there are the development and flexibility, resourcefulness. In this regard, one more function of Aitys in the process of communication is the development of critical thinking of youth, and also a new creative position in a communication process.